AutoCAD self-paced eCourse : AutoCAD 2D : ebook - Baumback, Wally; Vancouver Community College; BC Open Textbook Project; BCcampus (Vancouver Community College, 2020)
"The AutoCAD 2D eBook was written as a tool to guide and teach you to master AutoCAD. No two students learn at the same pace, therefore the eBook was written with competency-based modules. The competency-based modules are bite-size pieces that allows you to work at your own pace. They can be used to learn by distance education, correspondence, online, instructor-lead classes, or by individuals teaching themselves to use AutoCAD in their own home or office. This eBook was designed to be used on AutoCAD software that was designed for the Windows operating system. An editable, Pressbooks version of this textbook is under development"--BCcampus website.
This work is licensed under the Creative Commons Attribution International CC-BY.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes index.
"For AutoCAD 2015, 2016, 2017, 2018, 2019 and 2020."
Description based on online resource; title from pdf title page (viewed on April 30, 2020).
Keywords: AutoCAD; Computer-aided design; Computer graphics; Electronic books